The Concept of Usury in the Interpretation of Al-Mishbah Through a Contemporary Hermeneutic Approach - Khusna Khanifa, Nurma; Mukhlishin, Mukhlishin; Idayanti, Rini (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
Critical religious studies through a hermeneutic approach in the context of the study of the Qur'an as an effort to understand its contents, commonly known as tafsir. One of the interesting aspects of contemporary interpretation is the presence of tafsir al-Mishbāh by M. Quraish Shihab. Within its hermeneutical framework, it seeks to mediate differences of opinion by stating that some hermeneutical theories are considered acceptable in Islamic studies. The study of hermeneutics as a method of interpreting the text of the Qur'an in al-Mishbāh's tafsir on the verse on ribā. The methodology used is a qualitative approach, with a type of literature research that will later be described and analyzed using content analysis. The results of this study show that Quraish Shihab never forgets to include the meaning of vocabulary, munāsabah between verses, and asbābal-Nuzūl. His interpretation method uses the al-ijtihad al-hidā`ī approach. From this, it can be seen that there are characteristics of modern quasi-objectivism even though it is still imperfect. One of the studies of tafsir through hermeneutics with a quasi-objective modernist style regarding the verse on ribā cannot be separated from three reviews, namely, first, ribā or excess that is prohibited in nature (اَضْعَافًا مُّضٰعَفَةً). Second, مَابَقِيَ مِنَ الرِّبٰوٓا leave the remainder of ribā. Third, فَلَكُمْرُءُوْسُ اَمْوَالِكُمْۚ لَا تَظْلِمُوْنَ وَلَا تُظْلَمُوْنَ efforts to eradicate and stop the practice of ribā.